Practice Variability in Determination of Death by Neurologic Criteria for Adult Patients - Junn, Alexandra (Yale J Biol Med, 2019)
In 2010, the American Academy of Neurology (AAN) published updated official guidelines for specific practices involved in the determination of death by neurologic criteria for adult patients, otherwise known as brain death. Most states, however, do not have laws mandating the standard adoption of the AAN guidelines. The responsibilities for creating and implementing brain death determination policies thus falls on individual hospitals. As a result, significant variability in practice exists between hospitals and even between providers. This review highlights the ways in which and the extent to which adult brain death determination varies across the US, while also making the case that such persistent levels of heterogeneity call for improvements in standardizing training in brain death determination.